A review of investigation on 4-substituted 1,8-naphthalimide derivatives - Gudeika, Dalius (Elsevier Ltd., 2020)
In recent years, much attention has been paid to the design and preparation of new 4-substituted 1,8-naphthalimide architectures as well as to the studies of the properties of materials. Wide possibilities of changing the optical and fluorescence, thermal, electrochemical, electroluminescent, and photoelectrical properties of 1,8-naphthalimide compounds can be materialized by introducing different electron-donating or electron-accepting moieties at the C-4 position in the 1,8-naphthalimide unit. Many 4-substituted 1,8-naphthalimide derivatives were capable to form glasses with the glass transition temperature up to 254 °C with good morphological stability. Moreover, some of them displayed relatively good charge-transporting capabilities that were appropriated for balanced carrier injection in organic light-emitting diodes. At the same time, derivatives 4-substituted 1,8-naphthalimide have found application in other optoelectronic devices, such as organic light emitting diodes, organic solar cells, as well as in memory devices. This review article appeals to researchers, students and professionals who are interested in the synthesis studies and applications of 4-substituted 1,8-naphthalimides. The communities the review article appeals to include chemists, physicicists, material scientists electronic engineers.
DG acknowledges to the ERDF PostDoc project No. 1.1.1.2/VIAA/1/16/177. We are grateful to J. V. Grazulevičius for the valuable comments on the manuscript.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; 18-Naphthalimide; C-4 position; Electron-accepting; Electron-donating; Optoelectronic devices